ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA KELAS IX SMP PADA MATERI BANGUN RUANG SISI DATAR - Afifah Nevi Syahputri; Nita Hidayati (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research was to measure the level of mathematical connection ability of class IX junior high school students on the material of polyhedra solid geometry. The subjects were 23 students of grade IX JHS in one of Bekasi Regency who had been considered by mathematics teachers. The research method is qualitative-descriptive. The research instrument used was in the form of a description test of students' mathematical connection abilities as many as 6 questions containing indicators for connecting knowledge of concepts and procedures, between topics of mathematics, other sciences, and problems in real life. The results of data analysis show 1) high-ability students meet all the indicators that must be achieved, 2) moderate category students are unable to meet the indicators of connecting mathematics with real-life problems, and 3) low category students are unable to meet all the indicators implemented. The average percentage of mathematical connection abilities of class IX JHS students is 52% meaning that it is still low with 13 students in the low category, 6 students in the medium category, and only 4 students in the high category.